Functional significance of Micraspis discolor (F.) (Coccinellidae: Coleoptera) in rice ecosystem. (7th January 2013) - Shanker, C.; Mohan, M.; Sampathkumar, M.; Lydia, Ch.; Katti, G.
Abstract: Coccinellids are key predators that are conserved and augmented in agricultural ecosystems, to achieve biological control of pests. Actual quantification of field predation has not been attempted for many of the beneficial coccinellids. Numerous reports show coccinellids as opportunistic, feeding on a variety of food material in addition to their preferred prey. Micraspis discolor is the most abundant species of coccinellid in rice ecosystems and touted as a biocontrol option for brown planthopper (BPH), Nilaparvata lugens (Stal), a key pest of rice. However, it has been reported as both entomophagous and phytophagous. Native polyacrylamide gel electrophoresis (PAGE) was used to separate esterases from whole‐body homogenates of Micraspis and its prey viz ., green leafhopper (GLH) Nephotettix virescens (Distant), BPH N. lugens, whitebacked planthopper (WBPH) Sogatella furcifera (Horvath), aphid Rhopalosiphum padi L., thrips, Haplothrips sp., and pollen. Field‐collected beetles showed a range of bands, some corresponding with pollen and GLH, while others were different from prey offered, indicating a wider range of prey spectrum than envisaged. Feeding preference studies confirmed a preference for pollen and GLH in no‐choice ( H  = 20.724; P = 0.001) and multiple‐choice tests ( H  = 20.52; P < 0.001) and a significant preference for pollen over all insects offered in the paired‐choice test ( t  = 5.099; P = 0.007). The abundance of adult M. discolor in rice at flowering phase does not correspond to prey abundance in the field but rather reflects an inclination to pollen feeding more than entomophagy.